Enhanced recovery after surgery program alleviates neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients undergoing gynecological surgery - Xing, Naidong; Wang, Hongyan; Huang, Yan; Peng, Jin (Frontiers in Medicine, 2023)
Background To evaluate the efficacy of the enhanced recovery after surgery (ERAS) programs on the systemic inflammatory response (SIR) of patients following gynecological surgery, a randomized controlled trial was performed to compare the ERAS programs with the conventional perioperative care programs. Furthermore, novel SIR markers could be identified to evaluate the ERAS programs of gynecological surgery. Methods Patients undergoing gynecological surgery were randomly allocated to either the ERAS group or the conventional group. The correlations between the elements of ERAS protocols and SIR markers following gynecological surgery were evaluated. Results A total of 340 patients who underwent gynecological surgery were enrolled (ERAS = 170; conventional = 170). First, we identified whether the ERAS programs after gynecological surgery reduced the perioperative difference between neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). Interestingly, first flatus time postoperatively, visual analog scale (VAS) score of patients was positively correlated with the perioperative difference NLR or PLR. Moreover, we discovered that the perioperative difference NLR or PLR was correlated with elements of ERAS protocol, including first sips of water, first semifluid diet postoperatively, pelvic drain duration, and out-of-bed time of patients. Conclusion We originally reveal that certain elements of ERAS programs alleviated SIR to operation. The implementation of ERAS programs enhances postoperative recovery after gynecological surgery via improving system inflammatory status. NLR or PLR could be the novel and inexpensive marker to assess ERAS programs in gynecological surgery. Clinical trial registration:ClinicalTrials.gov, identifier, NCT03629626.